2018
DOI: 10.1377/hlthaff.2018.0112
|View full text |Cite
|
Sign up to set email alerts
|

Changes In Hospital Utilization Three Years Into Maryland’s Global Budget Program For Rural Hospitals

Abstract: In a substantial shift in payment policy, the State of Maryland implemented a global budget program for acute care hospitals in 2010. Goals of the program include controlling hospital use and spending. Eight rural hospitals entered the program in 2010, while urban and suburban hospitals joined in 2014. Prior analyses, which focused on urban and suburban hospitals, did not find consistent evidence that Maryland's program had contributed to changes in hospital use after two years. However, these studies were lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 23 publications
3
50
2
Order By: Relevance
“…That said, our results differ from those of Roberts et al in that we do find a significant decrease in outpatient visits. Their analyses use only Medicare fee‐for‐service data, while our analyses include all payers’ data.…”
Section: Discussioncontrasting
confidence: 99%
“…That said, our results differ from those of Roberts et al in that we do find a significant decrease in outpatient visits. Their analyses use only Medicare fee‐for‐service data, while our analyses include all payers’ data.…”
Section: Discussioncontrasting
confidence: 99%
“…Using all‐payer hospital claims data and a difference‐in‐difference design, Done and Herring found no changes in admissions, readmissions, or emergency department (ED) visits associated with the program after 3 years, but did find a statistically significant 14.8% reduction in non‐ED outpatient utilization. By and large, these findings echo those of two prior evaluations of Maryland's program in rural hospitals, which found no change in readmissions among all payers after 18 months, and no changes in inpatient and ED use in a Medicare‐only population after 3 years . All three studies of the rural program utilized within‐state comparison groups—comprised of populations served by Maryland hospitals that had yet to receive global budgets—to isolate the effect of hospital budgets from other policy changes unique to Maryland's hospital payment system, providing a robust framework with which to examine the impact of this payment model in rural settings.…”
Section: Global Budgets In Maryland Hospitals: Assessing the Evidencesupporting
confidence: 65%
“…Done and Herring's analysis of rural hospitals and a CMS‐funded evaluation of the statewide program found reductions in outpatient hospital utilization and spending, which was concentrated among non‐ED services where hospitals likely had the greatest ability to reduce volume . However, studies by Roberts et al . concluded that, in both rural and urban contexts, reductions in outpatient utilization constituted a continuation of pre‐global budget trends rather than a post‐policy effect.…”
Section: Global Budgets In Maryland Hospitals: Assessing the Evidencementioning
confidence: 99%
See 2 more Smart Citations